2018
DOI: 10.4103/ijem.ijem_707_17
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocholine PET imaging of parathyroid disease

Abstract: To give an overview of the potential clinical utility of 18F-fluorocholine PET/CT (FCH PET/CT) in imaging of parathyroid adenoma. Available studies have provided preliminary results of 18F-FCH PET/CT in primary and secondary hyperparathyroidism. Results of various studies have shown that 18F-FCH is a promising upcoming tracer for the detection of parathyroid adenomas, especially when multiple, or having low size. FCH PET/CT has the potential to be a standard investigation in the detection of parathyroid lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
0
26
0
3
Order By: Relevance
“…17-20 99m Tc-sestamibi scan (complemented with neck ultrasound) is still the most commonly used method in many countries. 18 Sestamibi is a small protein la-belled with the radio-pharmaceutical technetium-99m. The scan is performed by injecting small amount of radioactive material, which is then absorbed by overactive parathyroid gland.…”
Section: Clinical Presentation and Diagnosticsmentioning
confidence: 99%
See 4 more Smart Citations
“…17-20 99m Tc-sestamibi scan (complemented with neck ultrasound) is still the most commonly used method in many countries. 18 Sestamibi is a small protein la-belled with the radio-pharmaceutical technetium-99m. The scan is performed by injecting small amount of radioactive material, which is then absorbed by overactive parathyroid gland.…”
Section: Clinical Presentation and Diagnosticsmentioning
confidence: 99%
“…Different studies reported the sensitivity of 99m Tc-sestamibi between 77% and 89%, but up to one-third of patients with adenomas could be sestamibi negative. 18 PET/CT is a newer and promising tool for localization of parathyroid adenomas. Different PET tracers can be used ( 18 F-fluorodeoxyglucose, 18 F-fluorocholine (FCH) etc.).…”
Section: Clinical Presentation and Diagnosticsmentioning
confidence: 99%
See 3 more Smart Citations